Intergenerational Schooling Mobility and Macro Conditions and Schooling Policies in Latin America - Nancy Birdsall; Jere R. Behrman; Miguel Székely (Inter-American Development Bank, Office of the Chief Economist, 1998)
The effects of market and policy reforms on poverty and inequality in Latin America have been of considerable concern. The region continues to have relatively great income inequalities. Two different societies with the same income distribution may have different levels of social welfare because they have different degrees of social mobility. To date little attention has been paid to measuring social mobility in the region. Schooling is thought to be a major mechanism through which intergenerational social mobility is affected. This paper explores the strength of the association of family background with child schooling and whether the strength of this association is related to some major macro and aggregate school policy variables.
Keywords: 330; Soziale Mobilität; Allgemeinbildende Schule; Generationengerechtigkeit; Bildungsniveau; Schulpolitik; Lateinamerika